Premature infant parents’ Need at Neonatal Intensive Care Unit in Erbil City, Iraq: A descriptive cross-sectional Study - Kafia Hashim Karim; Norhan Zeki Shakir (Journal of the Pakistan Medical Association, 2023)
Objectives: To assess the perceived needs of parents who had premature infants in a neonatal intensive care setting. Method: The descriptive cross-sectional study was conducted at the Raparin Teaching Hospital for Children, Erbil, Iraq, from April to June 2021, and comprised parents with premature infants who were enrolled during their infants’ stay at the neonatal intensive care unit. Data was collected using a two-part questionnaire. The first part entailed an interview exploring socio-demographic data, while the second part was a self-report questionnaire adapted from the Critical Care Family Needs Inventory, and had five domains; support, information, proximity, assurance, and comfort. Data was analysed using SPSS 25. Results: There were 57 sets of parents and premature neonates. The mean gestational age of the neonates was 33.37±3.29 weeks, mean age of fathers was 31.44±7.24 years, and mean age of mothers was 27.51±6.19 years. Among the neonates, 31(54.4%) were boys, and 32(56.1%) had been delivered through caesarean section. Of the total 114 mother and father, 106(93%) required assurance, 98(86%) needed comfort, and 96(84.2%) confirmed proximity as the most essential need. Besides, 84(73.7%) required information and 79(69.3%) required support. Conclusion: Parents of premature infants hospitalised in neonatal intensive care unit needed assurance, comfort, proximity, information and support in order of priority. Key Words: Premature, Infant, Parents, Erbil.